PSYCHOLOGICAL ADAPTATION AND REHABILITATION OF RECIPIENTS OF DONOR ORGANS - S. V. Gautier; N. F. Klimusheva (Вестник трансплантологии и искусственных органов)
The paper analyzes the nature of psychological adaptation and rehabilitation of patients, recipients of solid organs. The results of the clinical and psychological work with patients, recipients of donor organs, carried out in theSverdlovskRegionalClinicalHospital№ 1 are shown. Special attention has been paid to the study of motivation as the main psychological factor in the process of adaptation and rehabilitation. We have also shown the infl uence of body image and self-evaluation on the emotional state of patients after the operation. Special stress is laid on the significance of psychological factors which improve the quality of the patient’s life. The main principles and the system of psychological rehabilitation are presented.